Weapon Bracket and Operators’ Table : Design of Weapon Bracket and Operators’ Table for the Infantry Combat Vehicle CV90 - Ferm, Martin (2015)
This master’s thesis project is the final course of the program Industrial Design Engineering with focus on product development at Luleå University of Technology (LTU) Luleå, Sweden.This master thesis project was carried out during the autumn of 2014 at the Department of Interior & Support Systems as a part of the engineering division at BAE System in Örnsköldsvik, Sweden. The project was divided into two separate objectives. The first objective with the project was to redesign products with respect to an overall improvement of the products geometry, weight, material, use and accessibility. The second objective was to design a product to explore the possibilities of implementing a lighter material as an alternative to steel. This thesis project focus on products that are a part of, or intended for the infantry combat vehicle called CV90.The first objective focused on the redesign and optimization of an operator’s table with the incentive to improve the weight, geometry, use- and accessibility of the table construction. The second objective focused on the design of a weapon bracket to implement a new lighter material. The project followed a traditional product development process. A process of literature research of decisive theory concerning methods and approaches, theories and guidance. Literature studies founded the base of this project and were followed by an ideation process, concept development, evaluation of concepts, mock-up manufacturing and evaluation and finally, prototype layout for manufacture.The result of the weapon bracket is presented as a concept prototype to be manufactured in a carbon fiber material. Carbon fiber provides an extremely strong and light material that weighs around 18% compared to the mock-up, manufactured in steel. The use of carbon fiber resulted in a decreased weight of the bracket from 1.45Kg to 0.26Kg. The weapon bracket uses a module system that enables a two directional mounting ability of the rifle. The locking mechanism consists of an integrated spring forced bolt ...